2005
DOI: 10.1194/jlr.m500092-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of high density lipoprotein generated by ABCA1 and ABCA7

Abstract: The assembly of HDL by helical apolipoprotein and cellular lipid was studied using HEK293 cells to which ecdysone-inducible human ABCA1 or human ABCA7 was transfected. Expression of both ABCA1 and ABCA7 was induced linearly proportional to ponasterone A concentration in the medium. In the experimental conditions used, the ABC protein expression levels limited the rate of lipid release when the apolipoprotein concentration was high, and the apolipoprotein concentration was rate-limiting when the ABC protein exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
62
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(71 citation statements)
references
References 44 publications
9
62
0
Order By: Relevance
“…Likewise, in our previous study, in which J774 macrophages expressing ABCA1 were incubated with human plasma apoA-I, the formation of more than one type of apoA-I-containing lipid particle was also observed (16). Similar sizes of HDL particles were observed when apoA-I was incubated with HEK293 cells (17) or CHO cells (18) transfected with ABCA1 and with several cell types, including human skin fibroblasts and CaCo-2 cells, in which ABCA1 expression was induced (18). The fact that the enhancement of ABCA1 activity in cells by either transfection or induction with agonists leads to nascent HDL particle heterogeneity is consistent with ABCA1 activity alone causing the formation of the various apoA-Icontaining particles.…”
supporting
confidence: 50%
“…Likewise, in our previous study, in which J774 macrophages expressing ABCA1 were incubated with human plasma apoA-I, the formation of more than one type of apoA-I-containing lipid particle was also observed (16). Similar sizes of HDL particles were observed when apoA-I was incubated with HEK293 cells (17) or CHO cells (18) transfected with ABCA1 and with several cell types, including human skin fibroblasts and CaCo-2 cells, in which ABCA1 expression was induced (18). The fact that the enhancement of ABCA1 activity in cells by either transfection or induction with agonists leads to nascent HDL particle heterogeneity is consistent with ABCA1 activity alone causing the formation of the various apoA-Icontaining particles.…”
supporting
confidence: 50%
“…However, several studies [17,31] demonstrated that the role of ABCA7 in lipid transport is secondary in comparison to ABCA1, the major cellular lipid export protein.…”
Section: Abca7mentioning
confidence: 99%
“…Experiments by Hayashi et al [17] demonstrated that ABCA7 generates mostly small cholesterol-poor HDL particles, whereas ABCA1 forms predominantly big cholesterol-rich particles. Moreover, knockout of ABCA7 function in mouse macrophages did not seem to affect phospholipid or cholesterol efflux to apolipoprotein A-I, while inactivation of ABCA1 resulted in a complete absence of efflux [31].…”
Section: Abca7mentioning
confidence: 99%
“…However, it was recently reported that ABCA7 also mediates HDL assembly in vitro in a similar manner to ABCA1 (50)(51)(52). Although this reaction may not significantly contribute to the regulation of plasma HDL concentration (53), it may be important locally as a back-up system for ABCA1.…”
Section: Findings With Tangier Disease and Probucol: Linkage Among Thmentioning
confidence: 99%